Phenotypic Resemblance to Neuropsychiatric Disorder and Altered mRNA Profiles in Cortex and Hippocampus Underlying IL15Rα Knockout - He, Yi; Yu, Yuxin; Li, Yanan; Duan, Weicheng; Sun, Zuoli; Yang, Jian; Kastin, Abba J.; Pan, Weihong; Zhang, Yan; Wang, Kang (Frontiers in Neuroscience, 2021)
Background Previous studies of the functions of IL15Rα have been limited to immune activities and skeletal muscle development. Immunological factors have been identified as one of the multiple causes of psychosis, and neurological symptoms have been described in IL15Rα knockout (KO) mice. Seeking to explore possible mechanisms for this in the IL15Rα–/– mouse brain, we analyzed gene expression patterns in the cortex and hippocampus using the RNA-seq technique. Methods IL15Rα KO mice were generated and littermate wildtype (WT) mice were used as a control group. A Y-maze was used to assess behavior differences between the two groups. The cortex and hippocampus of 3-month-old male mice were prepared and RNA-seq and transcriptome analysis were performed by gene set enrichment analysis (GSEA). Results Compared with the WT group, IL15Rα KO animals showed higher speed in the novel arm and more entrance frequency in the old arm in the Y-maze experiment. GSEA indicated that 18 pathways were downregulated and 13 pathways upregulated in both cortex and hippocampus from the GO, KEGG, and Hallmark gene sets. The downregulated pathways formed three clusters: respiratory chain and electron transport, regulation of steroid process, and skeletal muscle development. Conclusion IL15Rα KO mice exhibit altered expression of multiple pathways, which could affect many functions of the brain. Lipid biosynthesis and metabolism in the central nervous system (CNS) should be investigated to provide insights into the effect of IL15Rα on psychosis in this murine model.